Profit distribution and loss coverage rules for central banks - Daniela Bunea; Polychronis Karakitsos; Niall Merriman; Werner Studener (European Central Bank (ECB), 2016)
The issue of central bank profit distribution is both complex and often politically controversial. Based on the replies of 57 central banks worldwide to an ECB questionnaire, this paper analyses how profit distribution rules can affect the amounts distributed and the financial strength of central banks. The paper also investigates the link between profit distribution, accounting rules and financial strength. Research shows that central banks apply divergent rules as regards profit distribution and loss coverage. While they are not a measure of central bank performance, in the long run profits strengthen the credibility of central banks and contribute to their financial independence, whereas profit distribution rules that do not allow central banks to set up adequate reserves might have the opposite effect. The interaction of profit distribution rules and accounting rules also plays an important role in central banks achieving financial strength. Accounting frameworks can materially influence central banks' net results via their treatment of unrealised results and the creation of general risk provisions. Distribution policies can offset the volatility of distributed profits by recording changes in value in a separate account before calculating the amount of distributable profit. This paper also shows that central banks with less volatile distributable profits display higher ratios of equity to total assets over time. Finally, the paper examines the role of stakeholders in influencing the profit distribution regimes of central banks, and develops a non-exhaustive set of general principles that could be considered in relation to profit distribution frameworks, with the aim of strengthening the financial, and therefore institutional, independence of central banks.
Keywords: E37; E58; M48; 330; accounting framework; financial independence; financial strength; loss coverage; profit distribution